(untitled) (Psychology Travelogs, 2023)
The article describes the results of an empirical study of the peculiarities of perfectionism of adolescents. The relevance of the problem is due to the need to study perfectionism as a psychological phenomenon in more detail, since no extensive research has been conducted in Ukraine. For the study, the questionnaire of perfectionism severity in youth was chosen using O. Loza’s «Scale of Perfectionism» and R. Slynyi’s «Revised Scale of Perfectionism». The study took into account the following data: specialty of study; year of study. The results of the empirical study were processed by calculating the percentage of individuals by the levels of manifestation of the selected features, followed by a qualitative interpretation and meaningful generalization of the data obtained.According to the results of O. Loza’s «Scale of Perfectionism», the total sample of adolescents under study was characterized by a predominance of representatives with medium (54%) and high (28%) levels of personal standards of activity and relationships, low (45%) and medium (43%) levels of polarization of thinking, in which the main forms of expression of perfectionism are hyperperfectionism (18%) and constructive perfectionism (56%). In order to study the adaptability - maladaptability of adolescent perfectionism in the studied individuals, we reviewed and analyzed the results obtained using R. Sledge’s Revised Scale of Perfectionism. The majority of the total sample of adolescents under study are characterized by medium and high levels of expression of such components of perfectionism as «High standards» (43% - medium and 36% - high) and «Striving for order»(39% - medium and 43% - high), as well as low (39%) and medium (53%) levels of «Experiencing inconsistency with one’s own high standards». The main characteristics and levels of perfectionism in adolescents were identified. According to the results of the study of levels and forms of expression among the studied adolescents, it was found that future psychologists are characterized by constructive perfectionism (according to O. Loza’s method), which is characterized by a high level of personal standards and a low level of polarization of thinking. The most characteristic form is adaptive perfectionism (according to R. Sleny’s method), which is characterized by high scores on the «High Standards» and «Striving for Order» scales.